Post-Traumatic Stress Symptoms among Lithuanian Parents Raising Children with Cancer - Irina Banienė; Nida Žemaitienė (MDPI AG, 2020)
Background and objectives: The study aims to evaluate post-traumatic stress symptom expression among Lithuanian parents raising children with cancer, including social, demographic, and medical factors, and to determine their significance for the risk of developing post-traumatic stress disorder. Materials and methods: The study was carried out in two major Lithuanian hospitals treating children with oncologic diseases. The cross-sectional study included 195 parents, out of which 151 were mothers (77.4%) and 44 were fathers (22.6%). Post-traumatic stress symptoms were assessed using the Impact of Event Scale-Revised. To collect the sociodemographic, childhood cancer, and treatment data, we developed a questionnaire that was completed by the parents. Main study results were obtained using multiple linear regression. Results: A total of 75.4% of parents caring for children with cancer had pronounced symptoms of post-traumatic stress disorder. The female gender (β = 0.83, p < 0.001) was associated with an increased manifestation of symptoms, whilst higher parental education (β = −0.21, p = 0.034) and the absence of relapse (β = −0.48, p < 0.001) of the child's disease reduced post-traumatic stress symptom expression. Conclusions: Obtained results confirmed that experiencing a child's cancer diagnosis and treatment is extremely stressful for many parents. This event may lead to impaired mental health and increased post-traumatic stress disorder (PTSD) risk; hence, it is necessary to provide better support and assistance to parents of children with cancer.